INVESTIGATING VOCABULARY LEARNING STRATEGIES OF EFL UNDERGRADUATE STUDENTS AT INDRAPRASTA PGRI UNIVERSITY - Nurmala Hendrawaty (Deiksis, 2015)
There are many aspects connected with vocabulary learning so that English as a Foreign Language (EFL) learners have to know and understand vocabulary learning strategies to improve their vocabulary. A vocabulary strategy is a special instructional tool and way of going about directly or explicitly as well as independent word learning skills required to learn words independently. Dealing with the reasons, the main purpose of the present research is to investigate the use of vocabulary learning strategies employed by EFL undergraduate students in the third semester, academic year 2014/2015, majoring English Education at Indraprasta PGRI University. According to Schmitt’s classification, vocabulary learning strategies for this research are classified as determination, social, memory, cognitive, and metacognitive strategies. The research data were collected by using Schmitt’s Vocabulary Learning Strategies (VLSQ). There were 137 undergraduate students from semester III of English Education Program were involved in this research. The results of descriptive statistics showed that they were as medium strategy users with the mean score of 3.26 and standard deviation of 0.93 for overallstrategy use. Furthermore, the most frequently strategies used were metacognitive strategies while the least frequently strategies used were cognitive strategies.Keywords: Vocabulary Learning Strategies, EFL Undergraduate Students